Pengaruh Kompetensi, Independensi, Pengalaman Kerja, dan Akuntabilitas Auditor terhadap Kualitas Audit dengan Etika Auditor sebagai Variabel Moderasi (Studi Empiris pada Kantor Perwakilan BPKP Kalimantan Barat) - Sonia, Sonia (Jurnal KIAFE, 2026)
This study aims to examine the effects of competence, independence, work experience, and auditor accountability on audit quality, with auditor ethics as a moderating variable. The study was conducted at the Regional Office of the Financial and Development Supervisory Agency (BPKP) in West Kalimantan Province. This research employs a quantitative causal approach using primary data collected through questionnaires distributed to auditors. The sample was selected using purposive sampling and consisted of 32 auditors who had worked for at least one year. Data were analyzed using Structural Equation Modeling with a Partial Least Squares approach using WarpPLS 8.0. The results show that competence has a positive but insignificant effect on audit quality. Independence and accountability have positive and significant effects on audit quality, while work experience has a negative and significant effect on audit quality. Auditor ethics significantly moderates the relationships between competence, independence, work experience, and accountability with audit quality. Auditor ethics weakens the effects of competence and work experience on audit quality, but strengthens the effects of independence and accountability on audit quality. These findings indicate that audit quality in government internal auditing is influenced not only by auditors’ technical and professional attributes but also by the ethical framework that guides their judgment and conduct.